Are northern mockingbirds classic open‐ended song learners?. (15th July 2020) - Gammon, David E.
Abstract: The northern mockingbird ( Mimus polyglottos, Linnaeus) is considered a classic example of a species in which individuals learn songs throughout adulthood, but this assumption has not been tested rigorously. To assess whether mockingbirds should be categorized as open‐ended learners, I conducted a longitudinal study and a field‐based song‐tutoring experiment. I recorded songs from 15 free‐living, banded, adult males in an earlier year and a later year, and I classified 400 mimetic songs per year per individual, based on the species and vocalization type mimicked. For two of these "mimetic types, " I further classified all the song types of all individuals in their early and later samples. The number of song types increased significantly across years for both mimetic types, and the average number of observed mimetic types per individual was 46.4 and 47.7 in the early and late samples ( p  = .055). I found no evidence adults learned any tutor stimuli after six months of tutoring, but examples from the scientific literature suggest the tutoring regime might not have been adequate to pass the motivational threshold required for learning. I conclude that mockingbirds probably are open‐ended learners, but that future research is needed to verify experimentally that adults can indeed imitate novel song types. Abstract : The northern mockingbird ( Mimus polyglottos ) is considered a classic example of a species in which individuals learn songs throughout adulthood, but this assumption has not been tested rigorously. Longitudinal song data from 15 free‐living, banded, adult males in an earlier year and a later year showed limited evidence for song‐learning (paired t test, t14 = 2.09, p = .055). Furthermore, a field song‐tutoring experiment produced no evidence adults learned from tutors.